Being treated like "waste" during the "golden years": Practical-theological perspectives - Theron, Petria M. (HTS teologiese studies, 2014)
The South African Government published the Older Persons Act no. 13 of 2006. The objectives of the Act are inter alia to maintain and promote the status, well-being, safety and security of older persons, to maintain and protect their rights and to combat abuse of older persons. This act is indispensable, as the elderly (people of 65 and older) form a growing segment of the South African population (4.767% in 1996 − 5.019% in 2011). They are in many regards extremely vulnerable, as they often face negative views regarding older people, experience discrimination, abuse, neglect and exploitation. Many atrocities are committed against them and one hears horror stories of older people who are abused and/or neglected by their own children and/or other people. One could almost say that these people, during their so-called ‘golden years’, are treated like ‘human waste’. I will investigate this phenomenon and attempt to interpret it within the South African context. I will then identify certain biblical guidelines to orientate one’s attitude towards old age and the elderly. To conclude, I will propose strategies to prevent elder abuse and restore human dignity to them.